Technico-economic comparison of heat transfer fluids or thermal energy storage materials: a case study using Jatropha curcas oil - N’Tsoukpoe, Kokouvi Edem; Le Pierrès, Nolwenn; Seshie, Yao Manu (African Journal of Science Technology Innovation and Development 13(5):1-19, 2021)
Thermal oils are omnipresent in processes using heat at high temperature as heat transfer fluids (HTF) as well as thermal storage materials (TESM), particularly in concentrating solar plants. In this study, a methodology for technico-economic comparison of HTF and TESM is proposed. Jatropha curcas crude oil (JaCCO), a non-edible vegetable oil, which has recently been proposed as an alternative to well-established heat transfer fluids (HTFs), is compared to some of these HTFs from an economic point of view. Two case studies were considered for the assessment, using the features of a pilot μ-CSP plant: i) the oils are used only as a HTF or ii) they are used as a HTF and a TESM. The degradation rate of the oils was considered as a parameter. The results show that from a technical point of view, the oils exhibit similar performance. The economic analysis was mainly impacted by the cost of oil per kWh of stored energy. For the plant using the oils as HTFs only, JaCCO would always be 2 economically more attractive than the other oils if its replacement frequency is less than 8–25 times that of the other oils in the economic conditions assumed in this study
Keywords: heat transfer fluids; Jatropha curcas crude oil; solar concentrating power; technico-economic analysis; thermal storage; Yézouma Coulibaly; Engineering; Institut International d'Ingénierie de l'Eau et de l'Environnement (2iE); Burkina Faso; 2iE College of Engineering